2015
DOI: 10.1371/journal.pntd.0003786
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Estimating the Global Burden of Endemic Canine Rabies

Abstract: There are a number of errors in Table 3. The table legend should read: Breakdown of economic costs of rabies by cluster in millions of USD. The headings for columns six, seven, and eight are incorrect. They should be in the following order: Dog vaccination, Dog population management, Livestock losses. Please see the correct Table 3 below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
91
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(97 citation statements)
references
References 1 publication
3
91
1
2
Order By: Relevance
“…Canine rabies causes approximately 59000 human deaths globally (37266 deaths in Asia; 21509 in Africa and 182 in Latin America) (Hampson et al, 2015) and 50% of the death cases are reported in Asian and African regions (CDC, 2016). In Asia, India has the highest number of human death caused by rabies (WHO, 2016).…”
Section: Human Deaths By Rabiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Canine rabies causes approximately 59000 human deaths globally (37266 deaths in Asia; 21509 in Africa and 182 in Latin America) (Hampson et al, 2015) and 50% of the death cases are reported in Asian and African regions (CDC, 2016). In Asia, India has the highest number of human death caused by rabies (WHO, 2016).…”
Section: Human Deaths By Rabiesmentioning
confidence: 99%
“…Out of 36 rabies patients, just five survived rabies infection after showing symptoms, and the patients had undergone extensive treatment known as the Milwaukee protocol (Hemachudha et al, 2013). The Island of Bali in Indonesia has been undergoing a serious eruption of canine rabies since 2008 and has also killed about 78 people as of late September 2010 (Hampson et al, 2015). About 583.5 million USD is spent annually for rabies prevention (Knobel et al, 2005).…”
Section: Human Deaths By Rabiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Rabies is a serious public threat which remains neglected and under reported in many developing countries (Cleaveland, Lankester, Townsend, Lembo, & Hampson, 2014). More than 55,000 human deaths occur annually, mostly in Asia and Africa (Cleaveland et al, 2014;Abela Ridder, 2015;Fooks et al, 2014;Hampson et al, 2015;Knobel et al, 2005). Bites from domestic dogs account for 99% of all human cases worldwide (WHO, 2005), with majority of (>50%) deaths occurring in children under 15 years old (Knobel et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Rabies remains prevalent in developing countries. According to recent estimates (6)(7)(8), canine rabies still causes around 59,000 deaths and over 3.7 million disability-adjusted life years (DALYs) each year; this is five times the fatalities reported during the 2004-2005 Ebola epidemic in West Africa (9). The greatest risk of developing rabies falls upon the poorest regions of the world, especially in rural areas of Africa and Asia (1, 6,8), where vaccination of domestic dogs is not widely implemented and where access to PEP is most limited or unaffordable for target populations (10).…”
Section: Introductionmentioning
confidence: 99%